Analisis Pemikiran Pendidikan Islam Ibnu Khaldun Perspektif Modern - Ach. Nurholis Majid; Nur Lathifah Aini; Fathorrahman Fathorrahman (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2020)
Discussions and in-depth analyses of Ibn Khaldun's thoughts continue to be carried out and are relevant in the context of modernity. Ibn Khaldun's thoughts are not just a high concept and are quite a subject of debate, but they have also become an essential foundation in the world of education to this day. The important thing in Ibn Khaldun's thought is his effort to link precisely and consistently the development of education with the development of human potential (nature) to support the development of a human level under Islamic teachings. For this reason, this article will focus on studying Ibn Khaldun's concept of Islamic education from a modern perspective. This study used a qualitative approach to library research. Researchers deepen, study, and identify existing knowledge in the literature related to Ibn Khaldun's thoughts on Islamic education. The primary data source for this research is the book